Political Participation of Young Immigrants: Do National Identification and Discrimination Moderate the Relationship? - Hoffmann, Philipp (2025)
With nearly a third of the German population having a migration background, immigrant political participation is crucial for democracy and immigrants’ integration. Adults with a migration background tend to participate less than the majority population. The findings become less conclusive when focusing specifically on young adults. The socialization phase during youth and young adulthood lays the foundation for future political participation and thus holds significant importance. At the same time, established factors that explain political participation, such as socio-economic status, political interest, or political efficacy, may not yet be fully developed in young adults. The present study starts here and focuses on the conventional and unconventional political participation of young adults (ages 18–30) with and without a migration background in Germany. Specifically, we investigate the moderating effects of perceived discrimination and national identification, which play a key role in shaping immigrants’ political integration. We use the civic voluntarism model as our baseline and explanatory framework. It provides a foundation for understanding differences in political participation more broadly. For our analyses, we rely on data from the Children of Immigrants Longitudinal Survey in Four European Countries (CILS4EU-DE, wave 5; linear regressions). First, we find contrary effects of perceived discrimination on recruitment networks and unconventional participation: Positive for individuals with a migration background and negative for individuals without a migration background. Second, national identification weakens the positive impact of political interest among the majority population and of recruitment networks among immigrants. Lastly, we observe no moderating effects for resources and conventional political participation for either group.